2021
DOI: 10.1002/pol.20210410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pendant groups on the blood compatibility and hydration states of poly(2‐oxazoline)s

Abstract: Poly(2‐methyl‐2‐oxazoline) (PMeOx), poly(2‐ethyl‐2‐oxazoline) (PEtOx), poly(2‐n‐butyl‐2‐oxazoline) (PBuOx), and poly(2‐phenyl‐2‐oxazoline) (PPhOx) are selected as poly(2‐oxazoline) (POX) models to study the effect of pendant groups on their blood compatibility and hydration states. A comprehension of this can provide a perspective for understanding the biocompatibility of PMeOx and PEtOx in water‐polymer interactions and may inspire the development of novel blood‐compatible POX derivatives. The aforementioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…EGAm and RUM showed slightly higher platelet adhesion than that of AUM; however, no significant difference was found between the polymers and PMEA. We have shown that the number of platelets adhering to materials is strongly correlated with the amount of adsorbed fibrinogen and degree of conformational alteration thereof, even when using a number of polymers with varied chemical structures. ,, We have also reported that platelet adhesion to materials can be suppressed if the degree of conformational alteration of fibrinogen is suppressed. ,, Protein adsorption behavior from plasma to material surfaces has been reported to be kinetically and thermodynamically controlled, known as the Vroman effect. , This effect describes the initial adsorption of abundant but weak surface-active proteins from the liquid phase and their subsequent replacement by species that bind more strongly but are present at lower concentrations. This effect also explains the differences in the adsorption behavior of proteins on the material surface and the behavior of adhered cells that recognize the adsorbed proteins at the surface.…”
Section: Resultsmentioning
confidence: 99%
“…EGAm and RUM showed slightly higher platelet adhesion than that of AUM; however, no significant difference was found between the polymers and PMEA. We have shown that the number of platelets adhering to materials is strongly correlated with the amount of adsorbed fibrinogen and degree of conformational alteration thereof, even when using a number of polymers with varied chemical structures. ,, We have also reported that platelet adhesion to materials can be suppressed if the degree of conformational alteration of fibrinogen is suppressed. ,, Protein adsorption behavior from plasma to material surfaces has been reported to be kinetically and thermodynamically controlled, known as the Vroman effect. , This effect describes the initial adsorption of abundant but weak surface-active proteins from the liquid phase and their subsequent replacement by species that bind more strongly but are present at lower concentrations. This effect also explains the differences in the adsorption behavior of proteins on the material surface and the behavior of adhered cells that recognize the adsorbed proteins at the surface.…”
Section: Resultsmentioning
confidence: 99%
“…94 The hydration state and biocompatibility of these polymers can be tuned by controlling the side chain spacing 94,114,139–141 and changing the chemical structure of the side chains. 142–167…”
Section: Polymers From Monocyclic Alkenesmentioning
confidence: 99%
“…Therefore, many studies on the appropriateness of synthetic and biomaterials as the base material have also been carried out. Surface chemical modifications such as functional molecules as growth factors interact with cells [ 39 ], and are antithrombotic due to plasma treatment and water control for water wettability and protein adsorption modification [ 4 , 40 , 41 , 42 ]. Similarly, to induce endothelialization of the material surface early after transplantation, many approaches aim for antithrombotic by post modal modification of functional molecules to the material surface and blending into the material [ 43 ].…”
Section: Materials Used In Tevg Designmentioning
confidence: 99%